(untitled) (Journal of educational development exploration, 2026)
In the context of the connotative development of higher education in the new era, "cultivating people with morality" as the fundamental task of education points out the value direction for the cultivation of college students’ humanistic quality. As an important mechanism for implementing the fundamental task of cultivating people with morality, "three comprehensive education" provides methodological guidance for systematically promoting the cultivation of humanistic literacy. Humanistic literacy is the core of college students’ comprehensive quality, which is related to their spiritual growth, value cultivation and sustainable development. Based on the perspective of cultivating people with morality, taking the concept of "three comprehensive education" as the analytical framework, this paper examines the practical challenges faced by the cultivation of humanistic literacy of college students by sorting out the internal logical relationship between humanistic literacy and moral cultivation, and then systematically explores the practical path of cultivating humanistic literacy of college students from the dimensions of full collaboration, whole process integration, and all-round integration, in order to provide theoretical reference and practical reference for improving the quality of talent training in colleges and universities.